DPP4 inhibitors as a novel therapeutic strategy in colorectal cancer: Integrating network biology and experimental insights - Sanaa K. Bardaweel; Baraa Abu Sneineh; Rima Hajjo; Reema Abu Khalaf (PLoS ONE, 2025)
Colorectal cancer (CRC) ranks as the third most prevalent cancer worldwide and the second leading cause of cancer-related deaths. Despite advances in treatment, drug resistance remains a critical challenge. Dipeptidyl peptidase 4 (DPP4), a multifunctional cell surface protein, shows variable expression across malignancies and plays a role in cancer biology. DPP4 inhibitors, initially developed as antidiabetic agents, have demonstrated anticancer properties in several cancer types. In this study, network pharmacology analysis revealed that DPP4 inhibitors modulate critical cancer-associated pathways, such as proteoglycans in cancer, ECM(extracellular matrix)-receptor interaction, and PI3K-AKT (phosphatidylinositol 3-kinase–protein kinase B) signaling. Experimental data showed dose-dependent growth inhibition in four CRC cell lines treated with FDA (Food and Drug Administration)-approved and novel DPP4 inhibitors. Combination treatments with doxorubicin yielded synergistic effects, whereas those with 5-fluorouracil (5FU) were either synergistic or additive. The examined DPP4 inhibitors effectively suppressed colony formation in HCT-116 cells and induced apoptosis. Additionally, the inhibitors resulted in G0/G1 cell cycle arrest and significantly reduced the expression of CD26 (Cluster of Differentiation 26), Bcl-2(B-cell lymphoma 2), and VEGF (Vascular Endothelial Growth Factor) in HCT-116 cells. Our findings highlight the potential therapeutic utility of DPP4 inhibitors in CRC treatment, either as standalone agents or in combination with standard chemotherapeutics. Moreover, the computational insights provided herein enhance our understanding of the molecular mechanisms underlying the anticancer effects of DPP4 inhibitors, paving the way for their potential clinical application.